The Logic of Chinese Behaviors - Zhai, Xuewei (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents a discussion on Chinese people's internal and external psychologies and logics, as well as the respective stage of social development and cultural context they were raised in, and from sociological, social psychological, and cultural anthropological perspectives. In particular, the book explores the relationship between Chinese people's behaviors and China's social and cultural structure. It puts forward a theoretical framework for the analysis of Chinese social behaviors, which is based on the realistic aspects of Chinese people's day-to-day-lives. The book also concludes that any attempt to study Chinese psychologies and behaviors should "seek the constant among the changes, or at least those aspects that are hardest to change" and investigate the context and background, which can provide a point of departure for current and future research.
The Degree and Limit of Localization Research: How Far Can We Go -- Confucian Social Construction: Perspective and Methodology of Social Research in China -- Language Analysis: A Research Method that Cannot be Ignored -- The Homogeneity and Heterogeneity of Chinese Perspectives on "Face" -- Appendix: Looking at the Intellectuals in Fortress Besieged from the Heterogeneity of Face -- An Analysis of the Function of "Local Policy": The Power Game of Local and Organizational Leadership in China -- Chinese Value Orientation: Historical Classifications and Problems of Transformation -- Appendix: In an Era that Lacks Values, What Kind of Values Do the Chinese Need -- Balance in Chinese Interpersonal Networks: A Case Study -- Familism and Instrumental Reason: A Social Survey of Rural Areas in Southern Jiangsu -- "Human Feelings" and Systems: Balances or Checks-and-Balances: On the Representativeness of Case Studies -- Appendix: The Cunning of Shame Culture: Thoughts on a Survey -- The Chinese Interpersonal Relationship Model -- The Chinese People's Choices and Decisions in Social Behavior Orientation: On the Variables of the Local Social Action Model -- Appendix: Do the Chinese People Infight? From the Perspective of Local Social Action Theory -- Personal Status: From Proposing a Concept to Establishing a Local Daily Sociological Analysis Framework.
Keywords: Ethnology; Personality; Difference (Psychology).; Culture; Sociocultural Anthropology; Personality and Differential Psychology; Sociology of Culture